2000
DOI: 10.1109/76.845011
|View full text |Cite
|
Sign up to set email alerts
|

A cell-loss concealment technique for MPEG-2 coded video

Abstract: Audio-visual and other multimedia services are seen as important sources of traffic for future telecommunication networks, including wireless networks. A major drawback with some wireless networks is that they introduce a significant number of transmission errors into the digital bitstream. For video, such errors can have the effect of degrading the quality of service to the point where it is unusable. In this paper, we introduce a technique that allows for the concealment of the impact of these errors. Our wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(85 citation statements)
references
References 15 publications
0
85
0
Order By: Relevance
“…Refined temporal concealment (RTC) using weighted boundary match was presented by Xu et al [10], in which a lost MB is divided into four blocks and the set of candidate MVs is increased. To exploit the temporal correlation between frames in the estimation of MV, the decoder motion vector estimation (DMVE) algorithm was proposed in [15]. The outer boundary matching algorithm (OBMA), which is a variant of BMA, was studied in [16] with the conclusion that OBMA performs better than BMA for temporal concealment at the same level of complexity.…”
Section: Temporal Error Concealment (Tec)mentioning
confidence: 99%
“…Refined temporal concealment (RTC) using weighted boundary match was presented by Xu et al [10], in which a lost MB is divided into four blocks and the set of candidate MVs is increased. To exploit the temporal correlation between frames in the estimation of MV, the decoder motion vector estimation (DMVE) algorithm was proposed in [15]. The outer boundary matching algorithm (OBMA), which is a variant of BMA, was studied in [16] with the conclusion that OBMA performs better than BMA for temporal concealment at the same level of complexity.…”
Section: Temporal Error Concealment (Tec)mentioning
confidence: 99%
“…where PBM(dx,dy), PBM _up_region (dx,dy), and PBM _left_region [19]. BMA is a kind of error concealment method and mainly uses the boundary pixels of loose blocks to find the best matching block in the search range of a reference frame.…”
Section: Motion Estimation At Decoder With Pbmamentioning
confidence: 99%
“…The boundary matching algorithm (BMA) (Lam et al, 1993) is proposed to select the best MV among a set of candidate MVs. Zhang, Arnold & Frater (2000), Tsekeridou & Pitas (2000), Kung et al (2006), Wu et al (2008) presented different block matching techniques that estimate the MV based on the set of surrounding MBs of the lost MB. Salama et al (2000) modeled the motion field as a Markov random field (MRF) and found the maximum a posteriori (MAP) estimate of the lost MV given its neighboring MVs.…”
Section: Related Workmentioning
confidence: 99%